2007
DOI: 10.1002/hed.20626
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium fortuitum–induced persistent parotitis: Successful therapy with clarithromycin and ciprofloxacin

Abstract: Background. Parotitis caused by nontuberculous mycobacteria, a very rare disease entity, has never been reported to be caused by Mycobacterium fortuitum (M. fortuitum) in the literature.Methods and Results. An 8-year-old girl was seen with painful swelling of the right parotid gland despite antibiotic treatment of more than 1 month. Elevated serum amylase activity and diffuse contrast-enhanced CT of the parotid gland confirmed the diagnosis of parotitis. Histopathological study of specimens taken from the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It was suggested that most NTM infections of the parotid gland are caused by Mycobacterium ascending via Stensen's duct in the oral cavity 3 5. As the patient liked the garden, the NTM in the present case might have originated from soil on the patient's hand.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…It was suggested that most NTM infections of the parotid gland are caused by Mycobacterium ascending via Stensen's duct in the oral cavity 3 5. As the patient liked the garden, the NTM in the present case might have originated from soil on the patient's hand.…”
Section: Discussionmentioning
confidence: 70%
“…In our case, NTM was not detected in culture. However, we considered that the tumorous lesion observed in this case was caused by rare mycobacterial species such as M fortuitum 5 or M chelonae ,6 10 because the PCR analysis did not detect M avium or M intracellulare. It is difficult to detect various minor mycobacterial species as their detection is influenced by conditions such as the culture period, temperature and humidity 11.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…3,6,7 The yield of smears can be improved using sonographic assistance where diffuse changes in echo patterns are observed. 9 In patients with acquired immune deficiency syndrome, granuloma formation may be absent, or noncaseating granulomas are seen. 4 Confirmation by acid-fast staining of smears, especially in patients with HIV, may help in the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The first case of M. fortuitum parotitis was reported by Chen et al in 2007. 1 However, primary parotitis due to M. fortuitum remains rare. It may present as an acute inflammatory lesion or a chronic tumorous one, devoid of pain or tenderness though the overlying skin may be discolored.…”
Section: Discussionmentioning
confidence: 99%